Nutritional Values and Their Potential Applications in Food Products of Krabok Seed (Irvingia malayana) - Preecharram, Sutthidech; Phosri, Santi; Theansungnoen, Tinnakorn; Roschat, Wuttichai; Arthan, Supakorn; Lasopha , Sudkamon; Jandaruang, Jinda (Trends in Sciences, 2023)
This investigation examined the nutritional value, mineral content, total phenolic content, antioxidant activity and cytotoxicity of uncooked and cooked Krabok seeds. Proximate analysis was carried out to determine the nutrient composition of uncooked and cooked Krabok seeds. The average fat, protein, carbohydrate, moisture, ash, and fiber contents were found to be 75.42, 11.78, 6.72, 2.68, 1.85 and 1.54 %, respectively. The Folin-Ciocalteu method was employed for the quantitative analysis of total phenolic compounds. All 6 samples of Krabok seeds extracted, both cooked and uncooked, were extracted using hexane, ethyl acetate, and ethanol, and subjected to the test. All the extracted samples contained phenolic compounds, with amounts ranging from 29.10 to 130.26 µg GAE/mL. The highest levels of phenolic compounds were observed in the ethanolic extract of cooked Krabok seeds. The antioxidant properties were evaluated using the DPPH assay. The scavenging activity of the extracted Krabok seed samples ranged from 9.84 to 62.31 %. The ethanolic extract of uncooked Krabok seeds exhibited the highest antioxidant activity. To assess the toxicity of the Krabok seed extract, HaCaT, Vero and RAW 264.7 cell liness were employed using the MTT technique. The results revealed that cell survival remained above 80 % for all doses of both uncooked and cooked Krabok seed extracts. These findings suggest that Krabok seeds are a valuable source of fat and other essential nutrients. The crude ethanolic extract exhibited a significant amount of phenolic content and antioxidant activity. Therefore, it could be utilized in the production of snacks or cosmetics. HIGHLIGHTS Krabok seeds has high nutrients and energy value. Krabok seeds has high phenolic compounds and non-toxic to cells. Krabok seeds were thought to be an inexpensive source of nutrients and a reliable supply of prospective culinary ingredients. GRAPHICAL ABSTRACT